The effect of dairyshed effluent irrigation on the occurrence of plant pathogenic Pythium species in pasture - Waipara, N.W.; Hawkins, S.K. (New Zealand Plant Protection, 2000)
A preliminary survey of pastures sprayirrigated with dairyshed effluent revealed a significant increase in the population of plant pathogenic Pythium species isolated from both soil and roots In vitro pathogenicity tests showed the majority of these isolates to be pathogenic when inoculated onto the seedlings of white clover subterranean clover and perennial ryegrass although both clover species were more susceptible to Pythiuminduced disease than ryegrass